2005
DOI: 10.1093/aje/kwi202
|View full text |Cite
|
Sign up to set email alerts
|

Large Meta-Analysis Establishes the ACE Insertion-Deletion Polymorphism as a Marker of Alzheimer's Disease

Abstract: Apolipoprotein E epsilon4 (APOE*4) is the only fully established susceptibility allele for Alzheimer's disease. One of the most studied candidates is the insertion (I)/deletion (D) polymorphism (indel) of the gene for angiotensin I-converting enzyme (ACE). This study aimed to clarify its association with Alzheimer's disease. The meta-analysis included 39 samples, comprising 6,037 cases of Alzheimer's disease and 12,099 controls, using mainly primary data. Potential interactions with gender, age, ethnic group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
139
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(151 citation statements)
references
References 69 publications
8
139
1
3
Order By: Relevance
“…Numerous studies have shown that the I allele of ACE D/I polymorphism is associated with an increased risk of late-onset AD (Hu et al, 1999;Kehoe et al, 1999;Elkins et al, 2004;Lehmann et al, 2005) and that I polymorphism is associated with a decreased serum ACE level (Rigat et al, 1990). ACE activity in CSF from patients with a moderately severe senile dementia of the AD type has been shown to decrease to 41% of that in CSF from non-AD patients (Zubenko et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the I allele of ACE D/I polymorphism is associated with an increased risk of late-onset AD (Hu et al, 1999;Kehoe et al, 1999;Elkins et al, 2004;Lehmann et al, 2005) and that I polymorphism is associated with a decreased serum ACE level (Rigat et al, 1990). ACE activity in CSF from patients with a moderately severe senile dementia of the AD type has been shown to decrease to 41% of that in CSF from non-AD patients (Zubenko et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the I allele was associated with an increased risk for AD, whereas the D allele was associated with protection (20,21). Of potential mechanistic relevance, inheritance of the D allele has been associated with increased plasma ACE levels (22).…”
mentioning
confidence: 99%
“…For example, Goldstein et al report that ACE (In-del variant) may predict decreased proteinuria in response to ACE inhibitors for renal disease; according to our review, this variant may also be associated with risk for Alzheimer disease. 9 However, this variant also has 21 'one positive study' results, suggesting unconfirmed but potential associated risk for 21 other diseases. Also, in the TNF gene variant G308A, the drug response is immunosuppressive therapy for aplastic anemia and sensitivity to the seizure medication carbamazepine.…”
Section: Resultsmentioning
confidence: 99%